ANALYSIS OF PUBLIC SERVICE RECORDS MANAGEMENT AT IMMIGRATION OFFICCE CLASS I TPI YOGYAKARTA - Zaky Umar Rachman (TEMATICS: Technology ManagemenT and Informatics Research Journals, 2020)
Public service always gets special attention from the Immigration Office Class I TPI Yogyakarta as a government agency that has the task of providing immigration services to the community, the breadth of the work area that has led to the high number of services carried out which is then accompanied by the high number of public service archives created, one of the steps taken to deal with this is the use of information technology in the process of managing archives. In this study, we used qualitative-descriptive methods used to explain how the process of managing public service archives is owned and to get an idea of how information technology is implemented at the Immigration Office of Class I TPI Yogyakarta. The results found from this study are still found constraints on the process of managing public service archives which then cause the process of managing public service archives can’t be carried out properly, then related to the application of information technology devices in the Immigration Office Class I TPI Yogyakarta has been carried out in accordance with the prevailing rules but in its implementation, there are still obstacles especially related to human resources. Therefore, The Immigration Office class I TPI Yogyakarta needs to continue to improve to maximize the process of managing public service archives and maximize the use of information technology that has been implemented.